Validity of a Self-administered Questionnaire Version of the Transition Dyspnea Index in Patients with COPD. (2nd January 2017) - von Leupoldt, Andreas; Reijnders, Thomas; Schuler, Michael; Wittmann, Michael; Jelusic, Danijel; Schultz, Konrad
ABSTRACT: The transition dyspnea index (TDI) is among the most widely used instruments in chronic obstructive pulmonary disease (COPD) patients to measure changes in dyspnea over time. In its original version it is used as guideline for a structured interview to assess the impact of daily activities on dyspnea in the three subdomains: functional impairment, magnitude of task, and magnitude of effort. However, the TDI is sometimes used as a self-administered paper-and-pencil questionnaire. The validity of this questionnaire format has not been tested, which was the aim of the present study. We tested 190 patients with COPD at start and end of a 3-week inpatient pulmonary rehabilitation program (PR). Dyspnea was assessed with the modified Medical Research Council Scale (mMRC), a questionnaire version of the TDI, and an interview version of the TDI. Group means for the TDI questionnaire and interview version were widely comparable for the TDI summary score and the three TDI subdomains. The scores of both TDI versions were strongly correlated and showed comparable, but only weak, correlations with changes during PR in spirometric lung function and mMRC. Improvement in dyspnea after PR was observed in 89% of patients when using the summary score of the questionnaire TDI, but only in 34% of patients when using the mMRC. The results suggest that a self-administered questionnaire format of the TDI is an adequate instrument for assessing changes in activity-related dyspnea during PR in patients with COPD. The responsiveness of this instrument to effects of PR appears greater than the responsiveness of the mMRC.